Cinematic Virtual Reality: The Paradox of the Omniscient Viewer in Omnidirectional Space versus Artistic Authorial Control - Haqshenas, Media (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The future of audio-visual storytelling might transcend the limits of the screen, allowing the spectator to enter the story or even become the protagonist around whom the story unfolds. This could lead to an art form that fundamentally changes our media consumption habits. My overall research question in this paper examines whether virtual reality (VR), specifically the cinematic virtual reality genre, will become the next defining audio-visual medium. I approach this inquiry as an open question, attempting to identify distinct aesthetics of cinematic VR that sets it apart from cinema. The goal is to equip creators aspiring to produce narrative VR experiences with a comprehensive understanding of not only the possibilities but also the challenges involved in this format, as the title implies.